Mutation status of refractory to imatinib patients with chronic myeloid leukemia - E. G. Ovsyannikova; K. D. Kaplanov; T. Yu. Klitochenko; A. V. Misyurin; I. L. Davydkin; L. V. Zaklyakova; E. A. Popov; B. N. Levitan (Онкогематология, 2014)
Mutation status of 36 chronic myeloid leukemia (CML) patients in chronic phase with primary and secondary imatinib resistance was analyzed. BCR-ABL mutations identified by direct DNA sequencing. BCR-ABL kinase domain mutations were detected in 30.5 % (11 of 36) of those patients. Most of identified mutations were missense mutations: Q252H, M244V, G250E, Y253F/H, E255K/V, T315I, M351T, F359V, F359C, F486S. Patients with BCR-ABL mutations have significantly lower 4-year event-free survival compared with CML patients without mutations (18 % vs. 53 %; р = 0.003). The results can be used as reference information in deciding on therapy in imatinib resistant CML patients with clinically relevant BCR-ABL mutations.